Representation of Heaven and Hell as Reflections of Human Nature - Zakirova, Nigora (The Lingua Spectrum, 2025)
Each process is closely related to certain concepts and views. We can express this connection in terms of language, time, and space. It is fact that mankind has a unique form intelligence and is superior to other creatures. The development of their mind and perception are questions about the world that arise in them, and in the process of finding answers to them, they are gaining insights that they thought were not important. The increase in people's level of knowledge has a significant impact on their way of life. It even leads to deepening of religious and worldly thoughts. The presence or absence of the concepts of Hell and Paradise leads to changes in human nature. This article discusses the concepts of heaven and hell, and its main goal is to determine the place of these two concepts' impact on the human psyche in modern science and literature. There is also a task based on deep reasoning. At the level of human intelligence, scientific justification of religious concepts, which is the product of ancient traditions, by researching their connection with human nature. As a result of the study, the literatures related to the research topic or the same ones were selected and comparative, artistic analyzes were conducted on them. The results of the studies showed that the mystical concepts presented in these sources taken for research have a high impact on the fundamentals of the human psyche, expressing worldly closeness. Based on the results of scientific research, the human psyche continues to rise with worldly and religious knowledge over the years. Like the concepts of good and evil of people, the concepts of Heaven and Hell appear and show their form in their nature.